Construction of Human Settlement Environment Design Theory Based on Positive Psychology: Creating Multidimensional Happiness - Chatterjee, Kaushik (Journal of Progress in Civil Engineering, 2025)
This research paper explores the interplay between urban planning, architecture, and built environments in promoting physical, mental, and emotional well-being. Through examining well-being-centric design principles, the paper demonstrates how such considerations support healthier, happier, and more productive urban populations. The investigation delves into the impacts of built environments on human psychology and physiology, leveraging case studies and empirical research to uncover best practices in creating human-centric spaces. Particular attention is paid to aligning these principles with the United Nations Sustainable Development Goals (SDGs).